Haematological Profile and its Clinical Implications in Dengue Viral Infections (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Dengue fever is the most common arboviral disease in the world. Transmission to humans of dengue virus initiates a spectrum of illness, from inapparent to severe and sometimes lethal infections. Complete blood count (CBC) is an important part of diagnostic workup of patients. Comparison of various findings in CBC and peripheral blood film can help the physician in diagnosis, management and assessment of prognosis of the patients.Objectives: To find out the pattern of haematological findings in dengue infection.Methods: This cross sectional study was carried out on 62 dengue cases in CMH Savar from May to October 2019. Diagnosis of dengue was based on clinical features, haematological and biochemical findings and confirmed by serological tests. Haematological parameters analyzed include haemoglobin (Hb), haematocrit, total leucocyte count (TLC), differential leucocyte count (DLC), platelet count and peripheral blood film.Results: Important findings in haematological profile were haemoconcentration, raised haematocrit, low WBC count, early neutrophilia and late lymphocytosis, reactive lymphocytes in peripheral blood and thrombocytopenia. Haemoglobin ranged from 10.0-18.5gm/dl. Haematocrit was raised in 13(20.96%) cases. Thrombocytopenia (platelet count